Symptomatic Epidural Haematoma after Cervical Laminoplasty: A Report of Three Cases - Yoshimasa Takahashi; Tetsuro Sato; Hironori Hyodo; Tomomaro Kawamata; Eiji Takahashi (Journal of Orthopaedic Surgery, 2016)
Symptomatic epidural haematoma after cervical laminoplasty is rare. We report 3 patients who required emergency evacuation of an epidural haematoma. Timely diagnosis and removal of the haematoma is important to prevent neurological deficits. The causative factors in these patients were preoperative coagulopathy, hypertension, and the malfunction of a closed-suction drain.